Evaluation Of Standard Operational Procedure For Receivable Collection Of PT. XYZ - Elsa Mayori; Muhammad Irsyad Halim (Social Sciences Insights Journal, 2023)
The aim of this research is to evaluate the implementation of Standard Operational Procedures for Receivables Collection at PT. XYZ and knowing the obstacles and delivering. solutions and suggestions for PT. XYS receivable collection procedures. The research method uses qualitative descriptive analysis supported by data collection from observation, documentation and interviews. Meanwhile, the data analysis method used is the Champion method. The results of Champion's research stated that the Standard Operating Procedures were declared effective by the billing department with a percentage of 91.67%. However, there are still obstacles in the receivables collection process, namely the cash collection process carried out by the collector team is not completed. For this reason, the author advises companies to consider adding collector staff and collaborating with cash payment outlets.